不定积分基本公式与推导

不定积分基本公式与推导

1
 axdx=axlna+C,(ax)=axlna\int\ a^x\,dx=\dfrac{a^x}{lna} + C,\quad ({a^x})' = a^x lna
2
tanxdx=sinxcosxdx=1cosxd(cosx)=lncosx+C\int\tan x\,dx=\int\dfrac{sinx}{cosx}\,dx=-\int\dfrac{1}{cosx}\,d(cosx)=-\ln{|\cos{x}|} + C cotxdx=cosxsinxdx=1sinxd(sinx)=lnsinx+C\int\cot x\,dx=\int\dfrac{cosx}{sinx}\,dx=-\int\dfrac{1}{sinx}\,d(sinx)=\ln{|\sin{x}|} + C
3
1cosxdx=secxdx=cosx(cosx)2dx=cosx1(sinx)2dx=11(sinx)2d(sinx)=1(1+sinx)(1sinx)d(sinx)=12[11+sinxd(sinx)11sinxd(sinx)]=12ln1+sinx1sinx+C=12ln(1+sinx)2(cosx)2=ln1+sinxcosx=lnsecx+tanx+C\int\dfrac{1}{cosx}\,dx =\int\sec{x}\,dx\\ =\int\dfrac{cosx}{(cosx)^2}\,dx =\int\dfrac{cosx}{1-(sinx)^2}\,dx \\ =\int\dfrac{1}{1-(sinx)^2}\,d(sinx)=\int\dfrac{1}{(1+sinx)(1-sinx)}\,d(sinx) \\ =\dfrac{1}{2}[\int\dfrac{1}{1+sinx}\,d(sinx) - \int\dfrac{1}{1-sinx}\,d(sinx)] \\ =\dfrac{1}{2}ln|\dfrac{1+sinx}{1-sinx}| + C \\ =\dfrac{1}{2}ln|\dfrac{(1+sinx)^2}{(cosx)^2}|=ln|\dfrac{1+sinx}{cosx}| \\ =ln|secx + tanx| + C 1sinxdx=cscxdx=sinx(sinx)2dx=sinx1(cosx)2dx=11(cosx)2d(cosx)=1(1+cosx)(1cosx)d(cosx)=12[11+cosxd(cosx+1)11cosxd(1cosx)]=12ln1+cosx1cosx=12ln(sinx)2(1cosx)2=ln1cosxsinx=lncscx+cotx+C\int\dfrac{1}{sinx}\,dx =\int\csc{x}\,dx \\ =\int\dfrac{sinx}{(sinx)^2}\,dx =\int\dfrac{sinx}{1-(cosx)^2}\,dx \\ =-\int\dfrac{1}{1-(cosx)^2}\,d(cosx)=-\int\dfrac{1}{(1+cosx)(1-cosx)}\,d(cosx) \\ =-\dfrac{1}{2}[\int\dfrac{1}{1+cosx}\,d(cosx+1) - \int\dfrac{1}{1-cosx}\,d(1-cosx)] \\ =-\dfrac{1}{2}ln|\dfrac{1+cosx}{1-cosx}| \\ =-\dfrac{1}{2}ln\dfrac{(sinx)^2}{(1-cosx)^2} \\ =ln|\dfrac{1-cosx}{sinx}| \\ =ln|cscx + cotx| + C
4
(secx)2dx=tanx+C,tanx=(secx)2\int (secx)^2\,dx=tanx + C,\quad tanx'=(secx)^2 (cscx)2dx=cotx+C,cotx=(cscx)2\int (cscx)^2\,dx=-cotx +C,\quad cotx'=-(cscx)^2
5
secx  tanxdx=sinx(cosx)2dx=1(cosx)2d(cosx)=secx+C,(secx)=secx  tanx\int secx \; tanx\, dx= \int \dfrac{sinx}{(cosx)^2}\,dx=\int-\dfrac{1}{(cosx)^2}\,d(cosx)=secx+C, \quad (secx)'=secx\;tanx cscx  cotxdx=cosx(sinx)2dx=1(sinx)2d(sinx)=cscx+C,(cscx)=cscxcotx\int cscx \; cotx \,dx = \int\dfrac{cosx}{(sinx)^2}\,dx=\int\dfrac{1}{(sinx)^2}\,d(sinx)=-cscx + C, \quad (cscx)' = cscx - cotx
6
1a2+x2dx=1aarctanxa+C\int\dfrac{1}{a^2 + x^2}\,dx=\dfrac{1}{a}arctan\dfrac{x}{a} + C 1a2x2dx=arcsinxa+C\int\dfrac{1}{\sqrt{a^2 - x^2}}\,dx=arcsin\dfrac{x}{a} + C
7

三角函数换元
1x2a2dx  x=asect,dx=a  sect  tant  dt=1atant  asect  tantdt=sectdt=lnsect+tant+C回代  xsect=xa,tant=x2a2a=lnx+x2a2lna+C1=lnx+x2a2+C\int\dfrac{1}{\sqrt{x^2 - a^2}}\,dx \\ 令\; x=asect, \quad dx=a\;sect \; tant \; dt \\ =\int \dfrac{1}{atant} \; asect \; tant\, dt \\ =\int sect\, dt \\ =ln|sect + tant| + C \\ 回代 \; x sect=\dfrac{x}{a} ,\quad tant=\dfrac{\sqrt{x^2 - a^2}}{a} \\ =ln | x + \sqrt{x^2 - a^2}| - lna + C_1 \\ =ln | x + \sqrt{x^2 - a^2}| + C

1x2+a2dx  x=atant,dx=a  (sect)2  dt=1asect  a(sect)2,dt=sectdt=lnsect+tant+C回代  sect=x2+a2a  tant=xa=lnx+x2+a2+C\int\dfrac{1}{\sqrt{x^2 + a^2}}\,dx \\ 令\; x=atant, \quad dx=a\;(sect)^2 \; dt \\ =\int \dfrac{1}{asect} \; a(sect)^2, dt \\ =\int sect\, dt \\ =ln|sect + tant| + C \\ 回代 \; sect = \dfrac{\sqrt{x^2 + a^2}}{a} \; tant=\dfrac{x}{a} \\ =ln|x + \sqrt{x^2 + a^2}| + C a2x2dx  x=asintdx=acostdt=a2(cost)2dt=a2cos2t+12dt=a2(sin2t4+t2)+C回代  sin2t=2sintcost=2xa2x2a2t=arcsinxa=a22arcsinxa+x2a2x2+C\int\sqrt{a^2 - x^2}\, dx \\ 令\; x=asint \quad dx=acostdt \\ =\int a^2 (cost)^2\, dt \\ =a^2 \int \dfrac{cos2t+1}{2}\, dt \\ =a^2(\dfrac{sin2t}{4}+\dfrac{t}{2})+ C \\ 回代 \; sin2t=2sintcost=\dfrac{2x\sqrt{a^2-x^2}}{a^2} \quad t=arcsin\dfrac{x}{a} \\ =\dfrac{a^2}{2}arcsin\dfrac{x}{a} + \dfrac{x}{2}\sqrt{a^2 - x^2} + C
8

平方差
1x2a2dx=1(x+a)(xa)dx=12a[1x+adx1xadx]=12alnx+axa+C\int \dfrac{1}{x^2-a^2}\, dx \\ =\int \dfrac{1}{(x+a)(x-a)}\, dx \\ =\dfrac{1}{2a}[\int \dfrac{1}{x+a}\,dx - \int \dfrac{1}{x-a}\, dx]\\ =\dfrac{1}{2a}ln\dfrac{x+a}{x-a} + C

9

三角函数变换
(cosx)2dx=cos2x+12dx=sin2x4+x2+C\int (cosx)^2\, dx=\int \dfrac{cos2x+1}{2}\,dx=\dfrac{sin2x}{4}+\dfrac{x}{2}+ C
(sinx)2dx=1cos2x2dx=x2sin2x4+C\int (sinx)^2\, dx=\int \dfrac{1-cos2x}{2}\, dx=\dfrac{x}{2} - \dfrac{sin2x}{4} + C
(tanx)2dx=(secx)21dx=tanxx+C\int (tanx)^2\, dx=\int (secx)^2 - 1\, dx=tanx - x + C
(cotx)2dx=(cscx)21dx=cotxx+C\int (cotx)^2\, dx=\int (cscx)^2 - 1\, dx=-cotx - x + C